A STUDY OF KATIE STANDON, A FERAL CHILD CHARACTER IN “MOCKINGBIRD DON’T SING” - DEWANGGA, GITA AYU (Jurnal Ilmiah Mahasiswa FIB, 2013)
Psycholinguistics is the study about psychology and language. It also explains about how language is learned, produced, and processed. Psycholinguistics in Cognitive Science Period studies more about human in learning language as the nature, such as children who have stages in acquiring language. Children who do not go through these stages may get language disorder. One of language disorders is experienced by feral children. Feral Children are children who never get any input like normal human being so that they cannot do anything normally, especially in producing language. The writer focuses on the study of Katie as a feral child in Mockingbird Don’t Sing film. The aims of this study are to find out the linguistic characteristics of Katie and also the treatment to Katie.     This study uses qualitative approach because it analyses the phenomenon in children. Case study is applied in this study to get the detail description from the subject and the data of this study are linguistic characteristics and treatment of Katie as a feral child.     This study reveals that there are three types of linguistic characteristics of Katie as a feral child. Those are phonology, grammar, and semantic. The writer finds that Katie is actually still able to develop her language but it seems difficult because she already passes her critical period. From the film, the writer also finds that there are four types of treatment, those are focus on the individual profile, playing game, communication interactivity, and natural and rich communication. From those treatments Katie is able to communicate though she tends to use sign language.     The last, the writer suggests that the next researcher who wants to analyze feral child can specifically use theories of linguistic characteristics.Keywords: Psycholinguistics, A feral child, Linguistics characteristics, Treatment, Mockingbird Don’t Sing